The coronavirus disease of 2019 pandemic-associated stress among medical students in middle east respiratory syndrome-CoV endemic area: An observational study. Issue 3 (22nd January 2021) - Batais, Mohammed A.; Temsah, Mohamad-Hani; AlGhofili, Hesham; AlRuwayshid, Nawaf; Alsohime, Fahad; Almigbal, Turky H.; Al-Rabiaah, Abdulkarim; Al-Eyadhy, Ayman A.; Mujammami, Muhammad Hussain; Halwani, Rabih; Jamal, Amr A.; Somily, Ali Mohammed
Abstract : Abstract: The coronavirus disease of 2019 (COVID-19) pandemic significantly affected different life aspects, including healthcare communities and academic institutes. We aimed to assess the level of stress and risk factors among medical students and interns during the COVID-19 pandemic in the setting of the middle east respiratory syndrome -CoV endemic area. A questionnaire-based cross-sectional study was conducted on a randomly selected sample of medical students and interns. The questionnaire was anonymously self-administered to indicate perceive hygienic practice change, importance of viral prevention domestic hygiene, perceive adequacy of received information, perceived agreement to facilitators to alleviate covid stress, self-reported stress level, and generalized anxiety disorder score. A total of 322 returned the questionnaire (69.7% response rate). Participants had good knowledge regarding severe acute respiratory syndrome -CoV2 in multiple aspects, with an average score of 13.8 out of 14. Two-thirds (62.4%) of the students experienced mild anxiety, (23.9%) had moderate anxiety, (6.8%) had clinically high anxiety level, and another (6.8%) had a clinically very high anxiety level. The stress level, as reported by the respondents (on a 1-10 scale), showed a correlation with the Generalized Anxiety Disorder scale. We observed an increased level of social avoidance and hygienic practice facilitated by availability of hand sanitizers. Majority of the students receive information regarding COVID-19 from reliable and official resources Most students reported mild to moderate levels of anxiety, and was associated with enhancement of their universal precaution measures. The availability of alcohol-based hand sanitizers and the off-campus study were great relievers. The importance of reliable pandemic resources in educating students during pandemics is emphasized. Furthermore, this study indicate the importance of students' support services to address mental health and students' wellbeing in the era of pandemics.